Could BCG Vaccination Induce Protective Trained Immunity for SARS-CoV-2? - Covián, Camila; Retamal-Díaz, Angello; Bueno, Susan M.; Kalergis, Alexis M. (Frontiers in Immunology, 2020)
Trained immunity is a type of memory-like immune response induced by some vaccines, such as BCG, which can confer antigen-independent protection against a wide variety of pathogens. The BCG vaccine has been extensively used to protect against M. tuberculosis-caused diseases for almost a hundred years. Interestingly, this vaccine reduces children’s mortality caused by infections unrelated to M. tuberculosis infection, a phenomenon thought to be due to the induction of trained immunity. The SARS-CoV-2 pandemic has infected, as today April 3, 2020; 1,094,068 people globally, causing a major public health problem worldwide. Currently, no vaccine or treatment is available to control this pandemic. We analyzed the number of positive cases and deaths in different countries and correlated them with the inclusion of BCG vaccination al birth in their national vaccination programs. Interestingly, those countries where BCG vaccination is given at birth have shown a lower contagion rate and less COVID-19-related deaths, suggesting that this vaccine may induce trained immunity that could confer some protection for SARS-CoV-2.